Implementation Of Mobilization Support Nursing in Post-Operational Sectio Caesarian Patients With Physical Mobility Disorders - Isnar Agustin; Prahardian Putri; Muliyadi; Sri Endriyani; Lusi Oktaviani (Journal of Applied Nursing and Health, 2022)
Background: Sectio Cesarean (SC) is delivery to give birth to a fetus through surgery on the abdomen by slashing the uterine wall. Mothers after section Caesarea will experience impaired physical mobility, resulting in unfulfilled activity needs. Impaired physical mobility can be overcome through the implementation of mobilization support. Methods: This case study design uses a descriptive method. The sampling method used was a purposive sampling of as many as two respondents, namely postoperative Sectio Caesarea patients who underwent surgery at Muhammadiyah Palembang Hospital in March 2022. The case study data were taken using interviews, observation, and secondary data tracing, namely collecting data on the status, progress notes, checklists, and medical records. The analysis was carried out descriptively and presented narratively. Results: Mobilization support is effective in overcoming impaired physical mobility of postoperative Sectio Caesarea patients Conclusion: The results of the case studies illustrate the need to implement mobilization support to overcome impaired physical mobility in postoperative Sectio Caesarea patients to minimize complications.